Pengaruh Metode Hidrolisis Terhadap Karakteristik Kimia Senyawa Kalsium Hasil Ekstraksi dari Cangkang Telur Ayam: The Effect of Hydrolysis Methods on Chemical Characteristics of Extracted Calcium Compounds from Chicken Eggshells - Yurikke Julieta Permata Putri Sunarya; Yuni Kustiar; Nancy Siti Djenar; Ayu Ratna Permanasari (KOVALEN: Jurnal Riset Kimia, 2022)
Preparation of calcium compounds such as calcium hydroxide, calcium carbonate, and calcium oxide from chicken eggshells can be done through conventional methods that are cheaper and more practical, such as the sol-gel hydrolysis method and the coprecipitation method. In this study, the synthesis of calcium compounds from domestic chicken eggshells was carried out using two methods: the coprecipitation method and sol-gel method. Coprecipitation method consists of acid hydrolysis and alkaline hydrolysis. Sol-gel method consists of modification I and modification II. The AAS results showed that the calcium content from the hydrolysis of acids, alkaline, sol-gel modification I, and sol-gel modification II: 14.50%, 6.64%, 6.68%, and 9.93%, respectively. The FTIR showed that calcium compounds have four characteristic absorption bands, including O–H (3641.60 and 3448.72 cm-1) derived from Ca(OH)2 and H2O products, C=O (2981.95 - 1799 cm-1), and C–O (1448.54 – 874.68 cm-1) both of which from carbonate ions (CO3-) in CaCO3 both from eggshell and from the resulting calcium compounds, and Ca-O (711.73 cm-1) derived from CaO products. The results showed that the modification ll sol-gel method was the best because calcium compounds consisting of CaCO3, Ca(OH)2, and CaO were produced in a smooth texture, white color, and with the highest calcium content compared to other methods.